Tumescent local anesthesia with ropivacaine in different concentrations in bitches undergoing mastectomy: plasma concentration and post-operative analgesia - Abimussi, Caio J. X. [UNESP]; Menegheti, Thais M. [UNESP]; Wagatsuma, Juliana T. [UNESP]; Floriano, Beatriz P. [UNESP]; Arruda, Andre M. M.; Santos, Paulo Sergio Patto dos [UNESP]; Oliva, Valeria N. L. S. [UNESP] (Wiley-Blackwell, 2014)
Objective To compare two concentrations of ropivacaine administered for tumescent local anesthesia (TLA) in dogs undergoing mastectomy.Study design Prospective randomized clinical study. Animals Seventeen bitches of various breeds, aged 12 +/- 2 years and weighing 10 +/- 6.5 kg requiring total unilateral or bilateral mastectomy.Methods Dogs were premedicated with acepromazine (0.04 mg kg(-1)) and morphine (0.4 mg kg(-1)) intramuscularly. Anesthesia was induced with propofol (2.5 mg kg(-1)) and midazolam (0.2 mg kg(-1)) intravenously, followed by intubation and maintenance with isoflurane and TLA. Dogs were randomly allocated to receive TLA either with 0.1% ropivacaine (group G1) or with 0.05% ropivacaine (group G05). TLA was performed by insertion of a multihole needle under the skin and infusion of ropivacaine and lactated Ringer's solution at a fixed volume of 15 mL kg(-1). Ropivacaine concentrations in arterial blood were measured by high-performance liquid chromatography. Post-operative pain was assessed using two scales (University of Melbourne pain scale and a modified composite measure pain scale) and von Frey filaments, 4 hours after TLA and at 1 hour intervals until sensitivity was regained. A score above 30% of the maximum possible score was considered a positive indicator of pain.Results Peak plasma concentrations of ropivacaine were measured 240 minutes after TLA in G1. Low concentrations were measured in G05 for 60 minutes, with subsequent increase. Analgesic rescue and return of sensitivity occurred at 7 +/- 2.3 and 7 +/- 1.9 hours (mean +/- SD) after TLA for G1 and G05, respectively.Conclusions and clinical relevance Tumescent local anesthesia with ropivacaine provided satisfactory post-operative analgesia that lasted for several hours, with no difference in duration between the concentrations. No serious side effects were attributed to TLA. Results indicated that 0.05% ropivacaine provided adequate analgesia for mastectomy, however, more studies are required to support this conclusion.
Keywords: analgesia; dog; local anesthesia; ropivacaine